2009
DOI: 10.1101/lm.1605510
|View full text |Cite
|
Sign up to set email alerts
|

Stress impairs optimal behavior in a water foraging choice task in rats

Abstract: Stress is a biologically significant social–environmental factor that plays a pervasive role in influencing human and animal behaviors. While stress effects on various types of memory are well characterized, its effects on other cognitive functions are relatively unknown. Here, we investigated the effects of acute, uncontrollable stress on subsequent decision-making performance in rats, using a computer vision-based water foraging choice task. Experiencing stress significantly impaired the animals' ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…Many common housing and handling procedures can cause an animal’s stress levels to increase dramatically (for review see Balcombe et al, 2004). Stress is known to impair cognitive function (Arnsten, 2009), and thus it can alter the results of behavioral tests (Kaneto, 1997; Dawood et al, 2004; Graham et al, 2011). It has been shown that loud unexpected sounds can raise levels of stress-related hormones (Burow et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Many common housing and handling procedures can cause an animal’s stress levels to increase dramatically (for review see Balcombe et al, 2004). Stress is known to impair cognitive function (Arnsten, 2009), and thus it can alter the results of behavioral tests (Kaneto, 1997; Dawood et al, 2004; Graham et al, 2011). It has been shown that loud unexpected sounds can raise levels of stress-related hormones (Burow et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In so far as the amygdala is not involved in the performance of avoidance responses, it is presumed that fearful memories are coded elsewhere, presumably somewhere in the cortico-striate circuitry that participates in voluntary choice behaviour [23][24][25]. We thus distinguish between amygdala-coded 'emotional' fear, which determines reflex and emotional responses, and whatever extra-amygdalacoded factor causes avoidance of places associated with danger, which we will refer to as 'extra-amygdaloid fear'.…”
Section: Discussionmentioning
confidence: 99%
“…The brains were removed and stored in 10% formalin overnight and then kept in 30% sucrose solution until they sank. Coronal 50 mm sections were taken through the extent of the lesion, mounted on gelatin-coated slides and stained with cresyl violet and Prussian blue dyes (electronic supplementary material, figure S6) [23].…”
Section: (E) Histologymentioning
confidence: 99%
“…Recently, acute stress was shown to facilitate the development of social subordination during competitive encounters in animals (Cordero and Sandi, 2007) and to affect decision-making in both animals (Graham et al, 2010;Shafiei et al, 2012) and humans (Buchanan and Preston, 2014;Pabst et al, 2013). A role for stress might be particularly relevant in humans, as social and economic life is marked by increasing inequality and rising stress (Atkinson and Piketty, 2007).…”
Section: Introductionmentioning
confidence: 96%